Bonjour, Mr. Satie - De Paola, Tomie (New York : Putnam, 1991)
Through the diplomatic efforts of Uncle Satie, two talented Parisian artists end their feud.
School Library Journal
Book Links (A.L.A.)
Booklist
4.7
K-3
Keywords: Artists -- Fiction; Uncles -- Fiction; Paris (France) -- Fiction; Cats -- Fiction; Artists -- Fiction; Uncles -- Fiction; Paris (France) -- Fiction